Ingsun's Philosophy of Titip Tajug Lan Fakir Miskin: Pillars of the Indonesian Civilization - Sumarna, Cecep; Gunawan, Heri (International Journal of Science and Society, 2025)
The phrase "Ingsun titip tajug lan fakir miskin" is a legendary testament by Sunan Gunung Jati containing profound spiritual and social messages. This testament reflects the foundation of Islamic values in the Indonesian archipelago, which combine religiosity and social concern. In the contemporary context, this message remains relevant as a response to the assessment of the function of mosques and increasing social inequality. This study aims to examine the philosophical and sociological meaning of this phrase and explore its relevance in the development of a civilized and just society in the modern era. In addition, this study also aims to uncover the contribution of Islamic values in the development of an inclusive and religious social character. The method used is a qualitative descriptive with a hermeneutic and historical-cultural approach through literature studies and interpretation of cultural heritage and social practices of the community. The results show that Tajug (mosque) must be understood not only as a place of worship, but also as a center for community empowerment and social advocacy. The conclusion of the study emphasizes the importance of revitalizing Islamic boarding schools (pesantren) as a foundation for the development of a religious, just, and local wisdom-based society.